Improving Students’ Vocabulary Mastery by Using Pair Check Method at the Eighth Grade Students of Junior High School - Syafitri, Andini; P Swondo, Ashari (Universitas Pahlawan Tuanku Tambusai, 2025)
Teaching vocabulary especially to junior high school students must be full of patience because junior high school students often feel bored and have no interest and motivation in learning English vocabulary. We need a way to conquer this trouble. One of teaching method that may be used to educate them is the use of pair check method. The purpose of this study was to determine whether the application of the pair check method can significantly improve students' vocabulary mastery. This research was conducted using a classroom action research (CAR) design. The subjects were eighth grade students at SMP Swasta Al-Washliyah 26, Medan. Based on the analysis, students' scores improved in each test. The average pre-test score was 58,2. In post-test 1, the average student score was 70,4. And in post-test 2, the average student score was 89,8. From the observation and interview results, it was found that the teaching and learning process went very well, with students being more active and enthusiastic in learning. The students improved their vocabulary mastery by using the pair check method and gained new understanding of the teaching method the researcher used in vocabulary learning. The pair check method successfully creates a fun and interactive learning atmosphere, increasing motivation and active participation of students in the vocabulary learning process